Multiple-Input Single-Output Wireless Power Transmission System for Coal Mine - Duan Zhao; Enjie Ding; Xin Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In Wireless Power Transmission (WPT) systems, the proportion of energy received by the load is critical and the efficiency is the more significant parameter. The magnetic multiple input algorithms as well as many multiple overlapping coils structures in the transmitter side are proposed for the coal mine Internet of the Things (IOT) nodes. Different phase shifts cases for the input signal were considered to study their effect on the efficiency. Simulation results showed that the axial component of magnetic induction resulted from the multiple overlapping coils structure has preferable homogeneous distribution over the traditional single input coil. The proposed system achieved an efficiency value of 60 % for a receiver placed 40 cm away from a 4 coils transmitter comparing to an efficiency value of 50% for the same distance using a single coil transmitter. Simulation results shows that the proposed model is well adapted for the movable charging mode for the IOT nodes in coal mine. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5439